2001
DOI: 10.1007/s00464-001-8112-z
|View full text |Cite
|
Sign up to set email alerts
|

Oncologic implications of laparoscopic and open surgery

Abstract: Although instrumental manipulation and mechanical tumor cell spillage seem to play the major role in port-site metastases from laparoscopic cancer surgery, minimally invasive procedures are used more and more in the resection of malignancies. However, port-site metastases also have been reported after resection of colon cancer in International Union Against Cancer (UICC) stage I [2, 14]. Therefore, changes in the peritoneal environment during laparoscopy also might influence intra- and extraperitoneal tumor gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 8 publications
1
10
0
1
Order By: Relevance
“…Several experiments have been carried out looking at the type of insufflation used [9], physical manipulation of the tumor [7,9], aerolization of tumor cells [10], increased tumor invasiveness [13], and adherence of tumor cells to the disrupted peritoneum at the trocar sites [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several experiments have been carried out looking at the type of insufflation used [9], physical manipulation of the tumor [7,9], aerolization of tumor cells [10], increased tumor invasiveness [13], and adherence of tumor cells to the disrupted peritoneum at the trocar sites [8].…”
Section: Discussionmentioning
confidence: 99%
“…A report from 1998 has documented 160 port-site recurrences after laparoscopy [14]. Other investigators reported experimental studies trying to elucidate the potential mechanisms of this phenomenon [9]. In addition, there are also experimental data suggesting that laparoscopy increases the invasive capacity of pancreatic cancer cells [13].…”
mentioning
confidence: 99%
“…The most important mechanism in the pathogenesis of wound metastases seems to be instrumental manipulation of the tumor and mechanical spillage of tumor cells [8]. Nevertheless, there is evidence to suggest that carbon dioxide (CO 2 ) pneumoperitoneum (capnoperitoneum) creates conditions favorable to tumor growth.…”
mentioning
confidence: 99%
“…Apparently technical skills and the learning curve have a major impact on the occurrence of the port-site metastasis [6]. However, some evidence from in vitro and in vivo studies suggests that CO 2 , the most commonly used gas during laparoscopic procedures, may interfere with host factors in a way that can promote the growth of malignant tumors [7].…”
mentioning
confidence: 99%